Central nervous system involvement in individuals with RASopathies. Issue 4 (1st December 2022) - Weaver, K. Nicole; Gripp, Karen W.
Abstract: Central nervous system (CNS) anomalies are common in individuals with RASopathies. While certain findings, including relative or absolute macrocephaly, are typical for most RASopathies, other findings are more common in certain conditions, with rare low‐grade gliomas in Noonan syndrome (NS); Chiari 1 malformation and tethered cord in Costello syndrome (CS); and variable structural anomalies including heterotopia and hydrocephalus in cardio‐facio‐cutaneous syndrome (CFC). We performed a literature review and present aggregate data on the common and uncommon CNS manifestations in individuals with RASopathies. A gene‐based approach to defining risk for specific abnormalities may be considered. However, limited information on the CNS findings of rare RASopathies, such as autosomal recessive LZTR1 ‐related NS or PPP1CB ‐related NS with loose anagen hair (NSLH), is currently available. Thus, consideration of the RASopathies as a group of distinct syndromic conditions with shared underlying causes and overlapping clinical presentations remains relevant, and individuals with a RASopathy are at risk for many findings seen in these conditions.